2022
DOI: 10.3389/fonc.2022.964779
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immune checkpoint inhibitors-combined antiangiogenic drugs in the treatment of hepatocellular carcinoma: A systematic review and meta analysis

Abstract: BackgroundHepatocellular carcinoma is a pathological type of liver cancer and accounts for the majority of primary liver cancers. We conducted a meta-analysis to evaluate the efficacy and safety of immune checkpoint inhibitors in combination with antiangiogenic drugs in the treatment of hepatocellular carcinoma.MethodsWe searched scientific literature databases and clinical trials databases through May 2022 for required studies. Progression-free survival was taken as the main outcome, and overall survival, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…All statistical analyses in the meta-analysis were performed using the RevMan version 5.3 (The Cochrane Collaboration, Oxford, UK). The results of Chi-squared and I 2 tests were used to assess the heterogeneity and determine which analytical model (fixed-effect or random effect model) to use for data integration ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…All statistical analyses in the meta-analysis were performed using the RevMan version 5.3 (The Cochrane Collaboration, Oxford, UK). The results of Chi-squared and I 2 tests were used to assess the heterogeneity and determine which analytical model (fixed-effect or random effect model) to use for data integration ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, HPBC has long been established as the common malignant tumor in humans, with high malignancy and mortality rates. [13][14][15] Overwhelming evidence from epidemiological studies substantiates a close association between IBD and HPBC. For instance, a case-control study by Yuan et al 16 found a heightened risk of PC development in UC populations (OR = 1.18, 95% CI: 1.07-1.31).…”
Section: Introductionmentioning
confidence: 99%
“…HCC is widely acknowledged as the predominant subtype of primary liver cancer, followed by intrahepatic cholangiocarcinoma and extrahepatic cholangiocarcinoma. Indeed, HPBC has long been established as the common malignant tumor in humans, with high malignancy and mortality rates 13–15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have displayed that combination therapy achieved better survival benefits than alone [ 27 , 28 ]. Leap-002 and SHR-1210-III-310 study, global multicenter phase III clinical trials reported in ESMO 2022 have not been included in the previous research.…”
Section: Introductionmentioning
confidence: 99%